Students’ motivation - Mykhailova, Nelia (My University, 2012)
Educational psychology has identified two basic classifications of motivation - intrinsic and extrinsic. Intrinsic motivation arises from a desire to learn a topic due to its inherent interests, for self-fulfillment, enjoyment and to achieve a mastery of the subject. Extrinsic motivation is motivation to perform and succeed for the sake of accomplishing a specific result or outcome. Students who are very grade-oriented are extrinsically motivated, whereas students who seem to truly embrace their work and take a genuine interest in it are intrinsically motivated.
Keywords: selfconcept; intrinsic motivation; extrinsic motivation; academic motivation; perseverance; самоконцепція; мотивація внутрішня; мотивація зовнішня; наполегливість; кафедра іноземних мов професійного спрямування